(untitled) (Research, Society and Development, 2020)
Hydroxyapatite (HA) is a ceramic material present in human bones and teeth. Synthetic HA has osteointegration and biocompatibility properties and it is widely used in implants and prostheses. One of the ways to synthesize HA is by the hydrothermal method, an efficient method that allows the control of temperature and pressure, creating high crystallinity products. This research aimed to obtain the hydrothermal HA, which was analyzed under different characterization forms. The synthesis performed was based on France and Pereira (2000), with adaptations, where 3.71 g of calcium phosphate (Ca(H2PO4)2) and 2.54 g of calcium hydroxide (Ca(OH)2) were used, the reaction was made in a stove at 245 °C for two hours and with a heating rate of 5 °C/min. After the reaction, the HA was washed and dried in an oven at 60 °C for twenty four hours, the final mass obtained was 0.268 g. The obtained product was characterized by Raman light scattering, absorption in the infrared (IR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), Multimolecular Adsorption Theory (BET) and Scanning Electron Microscopy (SEM). Based on the results obtained in the analyzes and comparisons with experiences reported in the literature, the hydrothermal HA synthesis performed in this work was valid.